The generic hybridity in "L’Homme de la pampa" by Jules Supervielle - Feki, Kamel (Thélème. Revista Complutense de Estudios Franceses, 2017)
Critical hesitations which refer to L’Homme de la pampa through the use of several generic names reveal the presence of two appealing traits, namely the freeing of the imaginary, and poetic writing. Supervielle’s novella thus belongs to the hybrid genre called ‘‘poetic narrative’’. In addition to this first-degree generic hybridity, there is a second-degree form of hybridity, since the novel crossgenerically refers to the dream narrative, the humorous and parodic novel, and the allegorical narrative. This generic hybridity recalls the appearance of an original work that ultimately defines itself as “a prose-poem” “where prose and poetry are one,” or more still as “fugue”—marked by conflating the different topoi of narrative genres. This generic hybridity also makes of L’Homme de la pampa an open and ambiguous novel that requires the reader to listen intensively, and that leads to identifying signifiers that relate the history of Guanamiru to various narrative genres. Reading such a text involves a recreation of the novel where the tension of decoding is interwoven with the pleasure of the creation of meaning. The novel thus becomes “a text of pleasure” where “the language babel is no longer a punishment,” but the pledge of the “pleasure of reading”.